The Education Systems of Germany and Other European Countries of the 19th Century in the View of American and Russian Classics: Horace Mann and Konstantin Ushinsky - Ellis, Arthur; Golz, Reinhard; Mayrhofer, Wolfgang (International Dialogues on Education Journal, 2014)
The article deals with comparative studies of the American founder of the Common School and public education in the U.S.A., Horace Mann (1796-1859), and the founder of the Russian pedagogy and public school, Konstantin Ushinsky (1824-1870) . They were visiting several European education systems, in order to get inspirations for the reform activities in their own countries. In the early 19th century the education system in the German Kingdom of Prussia was considered the most progressive in Europe. The article shows what Mann, Ushinsky and others could learn from their comparisons, what they thought to be useful for their countries or what might be rather rejected. It is mostly about the question if and to which extent national educational experiences are importable, exportable and interchangeable. Some of the instructive findings of the American Horace Mann and the Russian Konstantin Ushinsky, but also their misconceptions are both historically relevant and of most currency.